Shaping social innovation in local communities: The contribution of intermediaries - Cibin, Roberto; Robinson, Sarah; Teli, Maurizio; Linehan, Conor; Maye, Laura; Csíkszentmihályi, Christopher (2020)
Participatory social innovation projects often involve the coming together of design researchers, community development groups, and community members to develop (often technological) solutions to social problems or challenges. “Intermediaries” are specific individuals and organisations who contribute to these projects by translating intentions, values and experiences between design researchers and communities. Previous research has not yet critically examined the role of intermediaries in such projects. This paper does so in a project carried out in rural areas of Europe, which sought to test and develop a technology to support the creation of FM community radio stations in isolated areas. We present the project as a biography of infrastructures to provide an account of intermediaries’ interactions during the project's unfolding. We find that how intermediaries shape the social base and ends of the project, and the interpretation of the technology involved, is influenced by their position, goals, and relationships in the process.
Keywords: Communauté d'innovation; Europe; Idéation, dialogue et maillage; Libre accès; Étude de cas